Benign solution-processed (BixSb1−x)2Se3 alloys for short-wavelength infrared mesoporous solar cells. Issue 31 (25th July 2022) - Kumar, Jitendra; Vana, Omer; Balakrishnan, Subila Kurukkal; Edri, Eran
Abstract : The short wavelength infrared (SWIR) region of the solar spectrum is underutilized, partly due to the limited availability of light absorbers for this region. Abstract : The short wavelength infrared (SWIR) region of the solar spectrum is underutilized, partly due to the limited availability of light absorbers for this region. Here, we report the synthesis of bismuth antimony selenide [(Bi x Sb1− x )2 Se3 ] alloys through a low-cost, low-temperature (310 °C) benign solution process. Twenty-three percent of Bi has been successfully incorporated in antimony selenide [Bi/(Bi + Sb) = 0.23], reducing the optical bandgap from 1.22 eV to 1.05 eV. A detailed study on the composition and structure of the (Bi x Sb1− x )2 Se3 deposits reveals that increasing the Bi ion content in the ink facilitated nucleation and growth in the solution, resulting in decreasing nanorods' diameter and length. The applicability of the developed method has been demonstrated by incorporating it in an FTO/ZnO/CdS/(Bi x Sb1− x )2 Se3 /spiro-OMeTAD/Au solar cell structure. Developing benign solution processes for light absorbers in the SWIR region may enable low-cost tandem photovoltaics.